How Many Videos are Cited in Academic Research: An Analysis of Indian Scholarly Publications - Pakira, Arpan Kumar; Nath, Amit; Mazumder, Jhantu (DESIDOC Journal of Library & Information Technology, 2024)
This research aims to measure the occurrence of videos cited in the research publications by Indian researchers. More specifically, we investigated the videos associated with scholarly publications and analysed the usefulness of those videos using computational methods. The bibliographic metadata was gathered from Scopus using advanced search techniques. A total of 2,121 publications cited 3,191 online videos during 2008-2022, but 2,736 videos were considered for further analysis due to discrepancies in video IDs. The free Google API for YouTube was used to extract video metadata from YouTube, and the raw data was edited and extracted using OpenRefine, an opensource data carpentry tool. The diagrams have been made using R Studio. The result indicates a linear growth of cited videos from 2008-2018; an exponential increase is observed from 2019 onwards. Most videos are cited from the Computer Science and Social Science disciplines, and journal articles are the most preferred document types that mention videos. The Education category videos are cited the most, and the channel TEDx Talks produced the maximum number of cited videos in research publications. The overall study shows that YouTube is emerging as a significant source of information for research and educational purposes.